From fields to fairways : classic golf clubs of Minnesota - Shefchik, Rick (University of Minnesota Press, 2012)
From retreats for the middle class to playgrounds for the rich, golf clubs have been sources of recreation, fellowship, and business for Minnesotans for more than a century. Minnesota's courses have hosted some of the sport's most dramatic tournaments and legendary players - including Bobby Jones, Arnold Palmer, Jack Nicklaus, and Tiger Woods - and its clubs have been deeply involved in the development and popularizing of golf throughout North America. From Fields to Fairways is the first book to thoroughly explore the history, architecture, and joie de vivre of Minnesota golf clubs.